Crust Goat Leather Dyeing using Mahogany (Swietenia mahagoni) Sawdust Extract and Coloring Time to Get the Best Results - Rahmawati, Dona; Wagiman, Wagiman; Sukartiko, Anggoro Cahyo (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Synthetic dyes used in the leather dyeing process contain allergenic and carcinogenic compounds. Natural dyes sourced from wood industry waste, namely mahogany sawdust can be a substitute for synthetic dyes with the advantages of being more economical, minimizing waste, and relatively safe for the environment. This study aims to determine the effect of the comparison of mahogany sawdust with hot water solvent and the duration of dyeing time on the characteristics of the extract and the best results of dyeing application on crust goat leather, using a Completely Randomized Factorial Design with 2 (two) factors and 3 (three) levels respectively. The first factor is the ratio of mahogany sawdust with solvent during Extraction, 1:5; 1:10 and 1:15 (w/v) and the second factor is the duration of dyeing time, 60, 90 and 120 minutes, each with two repetitions. Data analysis used ANOVA analysis of variance. This research activity resulted in a comparison of mahogany sawdust and water solvent with the best duration of dyeing time in producing colored goat leather products with the criteria of color absorption, rub fastness (wet and dry) and color shading. The results showed the analysis of the highest extract tannin content was 7,66 µg/mL at 1:5 (w/v) extract. The highest color absorption was in the dye extract 1:5 (w/v) and the lowest was in the dye extract 1:15(w/v), both at 60 minutes, 90 minutes, and 120 minutes. All natural dyes from mahogany sawdust showed good color fastness values with a scale above 3/5. The visual result of the dyeing process is reddish brown. Keywords: goat leather, mahogany sawdust, natural dyes, tannin